AB0304 EXTRA-ARTICULAR MANIFESTATIONS IN A COHORT OF PATIENTS WITH RHEUMATOID ARTHRITIS RECEIVING BIOLOGIC TREATMENT. (June 2019) - Brandy-Garcia, Anahy; Nack, Annika; Prior-Español, águeda; Holgado, Susana; Martínez-Morillo, Melania; Espinar, Maria Aparicio; Camins-Fàbregas, Jordi; Casafont-Solé, Ivette; Gifre, Laia; Sanguesa, Clara; Riveros, Anne; Olive, Alejandro; et al.
Abstract : Background: Extra-articular manifestations (EAM) in rheumatoid arthritis (RA) are more prevalent in patients with seropositive, nodular and long term disease. Around 40% of patients with RA can develop EAM, although the incidence has decreased with the "treat to target" strategy. Objectives: To describe EAM in a cohort of patients with rheumatoid arthritis. Methods: Retrospective descriptive study of patients diagnosed with RA between 2000 and 2018 who are currently under active biological treatment. Cardiovascular risk factors, baseline characteristics of RA and EAM during their evolution are collected. Statistical analysis is performed with SPSS 24. Results: We recruited 108 patients, 81.5% female, with mean age at onset of RA of 50 ±15 years (range 17-82). RF was positive in 84.3% and ACPA in 81.3%. Erosions were observed on hands or feet at diagnosis in 35.2%. Mean follow up period: 12±8 years. The most common initial treatment was methotrexate (82.4%) and 44.4% received other DMARDs: leflunomide (32.3%), hydroxychloroquine (16.2%) and others (9.1%). DAS28VSG at diagnosis was 4.15±1.18 (1.89-6.02) and at the introduction of the first biological drug it was 5.02 ±1.16 (mean years since diagnosis 6±5). The first biological drug was etarnecept (40.7%), followed by adalimumab (17.6%), abatacept (15.7%), rituximab (7.4%), tocilizumab (7.4%) and infliximab (4.6%). 57.4% discontinued the first biologic: secondary failure (58.1%) or adverse effects (20.6%). 65.7% (71 patients) developed some EAM during disease evolution and 14.8% appeared during the first year. During this first year, secondary Sjögren (37.5%) was the most frequent, followed by rheumatoid nodules (18.7%), EPID (18.7%) and osteoporosis (18.7%). Two or more EAMs were present in 33.3% of patients. Fifty-four patients (56.3%) did not present any EAM at the beginning of the biological treatment and 29.6% (21 patients) developed EAM afterwards, with an average of 1±3 years. Pulmonary involvement was the first EAM to appear after the onset of biological treatment, followed by anemia (both in the first year). Summarizing the data of all patients over time, the most frequent EAMs were: osteoporosis (28.7%, mean appearance: 5 years from diagnosis); secondary Sjögren syndrome (27.8%, mean 6 years); normochromic normochromic anemia (21.3%, mean 8 years) and pulmonary involvement (17.6%, mean 4 years), presented as EPID (63.3%), NINE (25%), NIU (8.3%) and pulmonary nodules (8.3%). Other EAM observed were: cutaneous involvement in the form of rheumatoid nodules (15.7%, mean 5 years); ophthalmological involvement (6.5%, mean 18 years) (PUK 2.8%, uveitis 1.9%, scleritis 0.9%, episcleritis 0.9%); amyloidosis (3.7%, mean 16 years) and vasculitis (2.4%, mean 14 years). Conclusion: EAM have a high prevalence in RA patients receiving biologic treatment ( 76.6%). A third part of patients had 2 or more EAMs. 14.8% develop the first EAM during the first year of evolution of RA and 30% in the first 5 years. The most frequent are osteoporosis and Sjögren's syndrome, according to what is described in the literature. Pulmonary involvement is the most rapid during the evolution of RA with an average of 4 years. References: [1] Marcucci E, Bartoloni E, Alunno A, Leone MC, Cafaro G, Luccioli F, et al.Extra-articular rheumatoid arthritis. Reumatismo. 2018Dec20;70(4):212-224 Disclosure of Interests: None declared